Evaluation of the use of Pycnoporus sanguineus fungus for phenolics and genotoxicity decay of a pharmaceutical effluent treatment - Renata Alberto de Morais Watanabe (Ambiente & Água - An Interdisciplinary Journal of Applied Science, 2012)
If not properly and efficiently treated, wastes produced by the chemical industry can contaminate the environment. Using fungi able to degrade organic compounds (e.g. phenol) seems to be a prominent method to treat pharmaceutical wastewaters, in particular, the white-rot fungus. The aim of this work was to treat pharmaceutical effluent by the Pycnoporus sanguineus fungus. Three effluent samples were collected in a pharmaceutical industry. The production of enzymes such as laccase and manganese peroxidase was determined. Their production increased throughout the treatment with the P. sanguineus fungus, reaching maximum concentration of 4.48 U.mL-1 (Effluent 1), 8.16 U.mL-1 (Effluent 2), 2.8 U.mL-1 (Effluent 3) and 0.03 Abs.min-1 (Effluent 2), respectively, during 96 hours of biological treatment. Genotoxic effects of the raw and treated effluents were also investigated using the in vivo mouse bone marrow micronucleus (MN) assay. Results showed the biological treatment reduced the frequency of MN, in a dose-dependent manner, when compared to untreated sample. The decreasing of around 20% and 45% of phenolics concentration was observed throughout the treatment, confirming that laccase production can be related to the degradation of toxic compounds present in the effluent. Therefore, the biodegradation by the P.sanguineus fungus seems a promising method for the mineralization of recalcitrant compounds present in pharmaceutical effluents.